Regioselective synthesis of 1, 5-disubstituted 1, 2, 3-triazoles by 1, 3-dipolar cycloaddition: Role of Er(OTf)3, ionic liquid and water. Issue 9 (28th February 2019) - Maiuolo, Loredana; Russo, Beatrice; Algieri, Vincenzo; Nardi, Monica; Di Gioia, Maria Luisa; Tallarida, Matteo Antonio; De Nino, Antonio
Graphical abstract: Highlights: Synthesis of 1, 5-disubstituted 1, 2, 3-triazoles under eco-friendly conditions. 1, 3-Dipolar cycloaddition catalyzed by Er(OTf)3 /[mpy]OTf/H2 O system. Highly recyclable catalytic system. Hypothetical mechanism to clarify the role of all partners. Abstract: A simple procedure to obtain 1, 5-disubstituted 1, 2, 3-triazoles, using the Er(OTf)3 /[mpy]OTf/H2 O catalytic system is described. The reaction proceeds through an eliminative azide–olefin cycloaddition (EAOC) offering a highly regioselective approach and good yields (81–94%). The advantages of this method include simple operations of work-up and the ability of the catalytic system to be re-used five times without an evident loss in yield. The role of IL and water were speculated, invoking also a probable ionic self-assembly (ISA) effect.